The EMPOWERMENT OF IIK KENDENGLEMBU THROUGH THE UTILIZATION OF CHOCOLATE PACKAGE AS INGREDIENTS FOR MAKING TRADITIONAL SCRUB - Ayu Purwaningtyas; Aprilia Divi Yustita; Riza Rahimi (Universitas Lancang Kuning, 2022)
Kendenglembu Glenmore Farm is a cocoa producing area in Banyuwangi. This plantation is managed by BUMN, namely PTPN XII. One of the results of cocoa processing is in the form of cocoa powder which is marketed through a variety of foods and beverages. These various foods and beverages are partly managed through IIK Kendneglemembu, hereinafter referred to as PKM partners. In the production process, it produces a by-product in the form of waste commonly known as chocolate cake. The properties contained in it are able to ward off free radicals which are very beneficial for the skin. Seeing this content, to add value to the chocolate cake, it is converted into a scrub. The scrub is made traditionally with the aim of protecting the skin from harmful chemicals. This PKM activity by the Poliwangi Lecturer Team was able to produce processed products from chocolate cake in the form of a traditional scrub which was packaged under the name Srikandi Lulur Traditional. This result is able to add to the list of processed variants that are very useful for partners.